The Effects of Vocabulary Mastery on Comprehending Maritime English Texts: A Case Study of Seafarers of Nautical Class - Ika Erawati (Widya Mandala Surabaya Catholic University, 2014)
To comprehend the larger units of text such paragraphs and stories, the seafarers have to understand first Maritime English (ME) vocabulary. The types of ME vocabulary can be divided into core vocabulary type, semi-technical vocabulary type, and maritime and/or technical vocabulary type. This case study involves eight (8) seafarers of nautical class at Merchant Marine Academy who were investigated in around six sessions of meeting. Maritime Vocabulary Mastery Test, classroom observation, questionnaire, interview and reading comprehension texts were the techniques to gather data to answer the research questions. The result found that the seafarers who had mastered the three vocabulary types indicated that they could perform better in comprehending ME texts than those who only mastered semi-technical and core vocabulary type. While, those who had only mastered core vocabulary type and those who had not mastered the three vocabulary type encountered more difficulties in comprehending ME texts because understanding ME texts requires both specific and general meaning of words. The more seafarers have mastery on the three types of maritime vocabulary, the less they encounter difficulties in comprehending ME texts.